IS THERE ALKALI-ALUMINUM COMPLEXING AT HIGH TEMPERATURES AND PRESSURES? - Anderson G.M. (My University, 1995)
A number of solubility studies of aluminous minerals in aqueous alkali hydroxide solutions at high pressures have been interpreted by proposing the existence of alkali-Al complexes under these conditions. This paper shows that all relevant solubility studies at 2 kb can be accommodated without recourse to such complexes, using stability constants of the Al-hydroxy complexes calculated with a density model and the data of Castet et al. (1993).